Lung adenocarcinoma in a patient with Lynch syndrome: a case report and literature review - Hodges, Alan; Sun, Kai; Sheu, Tiffany G.; Bernicker, Eric H. (Frontiers in Oncology, 2023)
This article presents a case of a 62-year-old Vietnamese woman with a history of Lynch syndrome (LS), who developed lung adenocarcinoma with EGFR L858R mutation. LS is an autosomal dominant cancer predisposition syndrome caused by a pathogenic germline variant in DNA mismatch repair genes, often leading to microsatellite instability. While LS is primarily associated with gastrointestinal, endometrial, ovarian, and urologic tract cancers, lung cancer accounts for less than 1% of LS-related cancers, with only six cases of LS-related lung cancer previously reported in the literature. The patient underwent multiple lines of treatment for her lung adenocarcinoma, including tyrosine kinase inhibitors, stereotactic body radiation therapy, pemetrexed and pembrolizumab, amivantamab, and fam-trastuzumab deruxtecan but all resulted in only partial response followed by progressive disease. This case highlights the complex interplay of genetic cancer predisposition syndromes and the development of spontaneous driver mutations in the disease course and subsequent management of tumors arising in these patients.